Sistem Pendeteksi Gerak Menggunakan Sensor PIR dan Raspberry Pi - Akbar Juliansyah; Ramlah Ramlah; Dewi Nadiani (Sekawan Institut, 2021)
Digital security and monitoring systems are entering a new era. Every industry is busy developing security systems according to their individual needs. What can be done is by providing a security perimeter around the assets to prevent unwanted things. There are currently many CCTV (Closed Circuit Television) based security systems; CCTV security systems also have less effective because they require more devices and large enough storage memory. Also, there are other solutions, namely systems that are built using PIR sensors and Raspberry Pi. The PIR sensor is used to detect infrared emissions from humans, so the target object is a human. The PIR sensor also receives heat radiation from humans, so when humans move, this sensor will receive changes in radiation emitted by humans. The purpose of this study is to simulate a solution to the problem of infrastructure design for the development of a physical asset security system using a Wireless Sensor Network and to find out how the security system works using a PIR sensor and Raspberry Pi Model B. The research method used is the Network Development Life Cycle (NDLC) approach. This study illustrates that the Raspberry Pi with hardware capabilities and Rasbian OS and the Python programming language support building a security system. The HC-SR501 PIR sensor can also detect moving objects from the right, left, and front. Email and SMS can be well integrated to produce reports according to the sensor's movement.